PERAN BADAN USAHA MILIK DESA (BUMDES) DALAM PENGEMBANGAN USAHA EKONOMI MANDIRI DI PEDESAAN DESA GANDON KECAMATAN KALORAN KABUPATEN TEMANGGUNG - , Sri Mustika Wardani; Totong Subina (PPM Sdirjianbang Akademi Militer, 2023)
In the reform era in 1999 Law 22/1999 (article 108) was issued – the issuance of this regulation was a change solution from the Government, namely to encourage the formation of business entities or institutions that are used to manage their resources efficiently. Then it was clarified by PP 72/2005 (article 78 paragraph 1) which states that